SAT-LB093 Salty Relationships with Bone: Not Calcium nor Vitamin D - Hew-Butler, Tamara (J Endocr Soc, 2019)
Previous studies demonstrated a positive relationship between blood sodium concentration and bone mineral density (BMD) in ultramarathon runners following a 100-mile race (1) and a negative relationship in walkers (treadmill walking for 45-minutes) following an oral sodium load (2). However, accurate assessment of sweat sodium concentration ([Na(+)]) was absent in those exercise studies. Therefore, the primary aim of these pilot data were to assess potential relationships between sweat [Na(+)] versus bone mineral content (BMC) at rest. We hypothesized that higher sweat [Na(+)] would be associated with lower BMC in athletes participating in a larger vitamin D supplementation trial. The current data represent a cross-sectional baseline assessment whereas: sweat [Na(+)] was obtained via pilocarpine iontophoresis (Wescor), total body BMC, fat and lean mass obtained via dual energy x-ray absorptiometry scan (Hologic), serum 25-OH vitamin D (25-OH-D) obtained via venipuncture (Cobas E Immunoassay), and dietary intake assessed via 3-month Food Frequency questionnaire (NutritionQuest). Twenty-two male (n=13) and female (n=9) collegiate basketball players completed baseline testing (20±2years). Significant relationships between total body BMC vs. sweat [Na(+)] (r=0.54;p=0.01) and total lean mass (r=0.93;p<0.01) were documented, but not between total BMC vs. 25-OH-D (r=-0.30;NS), vitamin D intake (r=-0.17;NS), calcium intake (r=0.16;NS), or sodium intake (r=0.22;NS). African-American athletes (n=14) had significantly lower 25-OH-D levels vs. Caucasian athletes (28±11 vs. 44±15ng/mL;p=0.01), respectively. Male vs. female differences noted in: sweat [Na(+)] (51±15 vs. 33±11mmol/L;p=0.006), total body BMD (1.35±0.11 vs. 1.19±0.06g/cm(2);p=0.001), fat mass (14.9±0.45 vs. 19.8±4.5kg;p=0.009) and lean mass (71.7±8.0 vs. 55.9±6.0kg;p<0.001). Total body BMC was positively related to sweat [Na(+)], and not calcium intake nor 25-OH-D in this small cohort of healthy collegiate athletes. However, the direction of this relationship was opposite of expected (i.e. higher sweat sodium losses would be associated with lower, not higher, bone mineral). These data cautiously suggest sweat sodium output may represent an extrarenal mechanism to excrete excess sodium ingested. We believe these pilot data are worthy of expansion, involving rigorous endocrine evaluation, and of particular relevance to African-Americans with paradoxically low 25-OH-D and high BMD. References: (1) Hew-Butler T, Stuempfle KJ and Hoffman MD. Bone: an acute buffer of plasma sodium concentration during exhaustive exercise? Horm Metab Res. 2013; Sep;45(10):697-700. (2) Hew-Butler T, Angelakos K, Szczepanski J. Sodium Loading, Treadmill Walking and the Acute Redistribution of Bone Mineral Content on Dual X-ray Absorptiometry Scans. Am J Physiol Regul Integr Comp Physiol. 2019 Jan 1;316(1):R59-R67. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.